Emotional Representation in Video Clips. Feast 'O, Tuan': Roland Barthes's Visual Semiotic Analysis - Anfaisa Ibnu Danan Jaya; Sidiq Setyawan (Journal of Communication Studies, 2026)
The development of digital technology has transformed music videos into audiovisual media capable of constructing emotional and cultural meanings through visual symbolsm, lighting, gestures, and cinematic narration. One of the Indonesian music videos that strongly represents emotional experiences is "O, Tuan" by . Feast, which presents themes of loss, grief, and death through dark visual symbolism. This study aims to analyze how emotional representations of loss and death are constructed through visual signs in the music video 'O, Tuan' using Roland Barthes' semiotic approach. The study employed a qualitative descriptive method with primary data obtained through observation and documentation of scenes from the music video, while secondary data were collected from books, journals, and related literature. Data were analyzed using Roland Barthes' semiotic framework through denotative, connotative, and mythological interpretation of visual and verbal signs. The findings showed that emotional meanings were constructed through dominant low-key lighting, dark color palettes, non-verbal expressions, and spatial symbolism. The music video represents stages of grief, including denial, emotional emptiness, trauma, and acceptance. This study concludes that 'O, Tuan' functions as an audiovisual medium that represents complex emotional experiences related to grief and death. This study contributes to the development of visual semiotic studies in Indonesian popular music by demonstrating how audiovisual symbolism constructs emotional representations of grief and death.